2006
DOI: 10.5194/acp-6-2513-2006
|View full text |Cite
|
Sign up to set email alerts
|

Closure between measured and modeled cloud condensation nuclei (CCN) using size-resolved aerosol compositions in downtown Toronto

Abstract: Abstract. Measurements of cloud condensation nuclei (CCN) were made in downtown Toronto during August and September, 2003. CCN measurements were performed at 0.58% supersaturation using a thermal-gradient diffusion chamber, whereas the aerosol size distribution and composition were simultaneously measured with a TSI SMPS and APS system and an Aerodyne Aerosol Mass Spectrometer (AMS), respectively. Aerosol composition data shows that the particles were predominately organic in nature, in particular for those w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
94
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(107 citation statements)
references
References 58 publications
12
94
1
Order By: Relevance
“…This contrasts with urban closure studies indicating insoluble organics (Lance et al, 2009), especially at small sizes (e.g. Broekhuizen et al, 2006;Cubison et al, 2008;Quinn et al, 2008), although this can also be true for remote locations . Here we conduct a study of the hygroscopicity of the organic component at supersaturated conditions, focusing on the oxygenated component under the assumption that the unoxygenated component is non-hygroscopic.…”
Section: Introductioncontrasting
confidence: 44%
See 3 more Smart Citations
“…This contrasts with urban closure studies indicating insoluble organics (Lance et al, 2009), especially at small sizes (e.g. Broekhuizen et al, 2006;Cubison et al, 2008;Quinn et al, 2008), although this can also be true for remote locations . Here we conduct a study of the hygroscopicity of the organic component at supersaturated conditions, focusing on the oxygenated component under the assumption that the unoxygenated component is non-hygroscopic.…”
Section: Introductioncontrasting
confidence: 44%
“…Similar results have been published for subsaturated conditions (McFiggans et al, 2005;Raatikainen et al, 2010) and more recently for laboratory and ambient measurements ), although laboratory experiments have shown that organic aerosol hygroscopicity under subsaturated conditions can be lower than under supersaturated conditions (Petters et al, 2009b;Prenni et al, 2007;Wex et al, 2009). This study builds on the results from previous closure studies conducted in our group at urban and rural sites (Broekhuizen et al, 2006;Chang et al, 2007). (Rupakheti et al, 2005).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Broekhuizen et al (2006) and Cubison et al (2008) both show evidence that CCN closure can be improved with knowledge of size-dependent composition. Cubison et al (2008) also found that assumptions about the aerosol mixing state (internal or external) can adversely impact CCN predictions.…”
Section: Ccn Closure Reviewmentioning
confidence: 99%